2022
DOI: 10.3390/polym14224835
|View full text |Cite
|
Sign up to set email alerts
|

Automated Parallel Dialysis for Purification of Polymers

Abstract: The implementation of a dialysis method for the simultaneous purification of different polymer materials in a commercially available automated parallel synthesizer (APS) is discussed. The efficiency of this “unattended” automated parallel dialysis (APD) method was investigated by means of proton nuclear magnetic resonance (1H-NMR) measurements, which confirmed that the method enables the removal of up to 99% of the unreacted monomer derived from the synthesis of the corresponding polymers in the APS. Size-excl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…27 Terzioglu et al demonstrated, shortly aer, the strength of the dialysis method in an automated setup for high throughput screening for synthesising a polymer library using sophisticated parallel synthesis equipment. 28 For this work, a simple, comparatively cheap and reusable setup was built to produce multiblock copolymers via RAFT polymerization in a continuous ow process without the disturbing interference of residual monomers affecting the block copolymer delity. This approach solves the issues previously encountered by Baeten et al, 14 yet is much faster than any other Fig.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…27 Terzioglu et al demonstrated, shortly aer, the strength of the dialysis method in an automated setup for high throughput screening for synthesising a polymer library using sophisticated parallel synthesis equipment. 28 For this work, a simple, comparatively cheap and reusable setup was built to produce multiblock copolymers via RAFT polymerization in a continuous ow process without the disturbing interference of residual monomers affecting the block copolymer delity. This approach solves the issues previously encountered by Baeten et al, 14 yet is much faster than any other Fig.…”
Section: Introductionmentioning
confidence: 99%
“… 27 Terzioğlu et al demonstrated, shortly after, the strength of the dialysis method in an automated setup for high throughput screening for synthesising a polymer library using sophisticated parallel synthesis equipment. 28 …”
Section: Introductionmentioning
confidence: 99%